ARHI (DIRAS3), an imprinted tumour suppressor gene, binds to importins and blocks nuclear import of cargo proteins. Issue 3 (15th December 2009) - Huang, Shaoyi; Soon Chang, In; Lin, Wenbo; Ye, Wenduo; Luo, Robert Z.; Lu, Zhen; Lu, Yiling; Zhang, Ke; Liao, Warren S.-L.; Tao, Tao; Bast, Robert C.; Chen, Xiaomin; et al.
Abstract : ARHI (aplasia Ras homologue member I; also known as DIRAS3) is an imprinted tumour suppressor gene, the expression of which is lost in the majority of breast and ovarian cancers. Unlike its homologues Ras and Rap, ARHI functions as a tumour suppressor. Our previous study showed that ARHI can interact with the transcriptional activator STAT3 (signal transducer and activator of transcription 3) and inhibit its nuclear translocation in human breast- and ovarian-cancer cells. To identify proteins that interact with ARHI in nuclear translocation, in the present study, we performed proteomic analysis and identified several importins that can associate with ARHI. To further explore this novel finding, we purified 10 GST (glutathione transferase)–importin fusion proteins (importins 7, 8, 13, β1, α1, α3, α5, α6, α7 and mutant α1). Using a GST-pulldown assay, we found that ARHI can bind strongly to most importins; however, its binding is markedly reduced with an importin α1 mutant that contains an altered NLS (nuclear-localization signal) domain. In addition, an ARHI N-terminal deletion mutant exhibits greatly reduced binding to all importins compared with wild-type ARHI. In nuclear-import assays, the addition of ARHI blocked nuclear localization of phosphorylated STAT3. ARHI also inhibits the interaction of Ran–importin complexes with GFP (green fluorescent protein) fusion proteins that contain an NLS domain and a β-like import receptor-binding domain, thereby blocking their nuclear localization. By conducting GST-pulldown assays, we found that ARHI could compete for Ran-importin binding. Thus ARHI-induced disruption of importin-binding to cargo proteins, including STAT3, could serve as an important regulatory mechanism that contributes to the tumour-suppressor function of ARHI.